PENGARUH COMMITMENT ORGANIZATIONAL DAN (POS) TERHADAP KINERJA KARYAWAN MELALUI (OCB) PADA PT. NASMOCO KALIGAWE - Pusparini, Paramitha Agdina; Farida, Naili; Widiartanto, Widiartanto (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
The research was motivated by the decrease in the sales division employees at PT. Nasmoco Kaligawe annually. In addition, many employees who complained about the lack of support in the organization of work, coupled with the level of employee performance in achieving sales targets fluktuatif. The aim of this research is conducted to determine the influence of commitment organizational and perceived organizational support to company performance through organizational citizenship behavior. The population is all of employees of the sales division. The sample are 60 person of employees of sales division, with sample technique used was sensus sampling. The analysis used in this research is the Path Analysis using software SPS 15.0, which previously tested the validity, reliability, correlation coefficient, simple and multiple regression analysis, the coefficient of determination, and signification test (t test and F test) first. The result of this research approved that commitment organizational (X1) and perceived organizational support (X2) partially or simultaneously can influenced organizational citizenship behavior (Y1) and employee performance (Y2). According the result of path analysis showed that organizational citizenship behavior variable is intervening variable towards employee performance in this research.